Transforming the first-year engineering experience through authentic problem-solving: taking a models and modeling perspective. - Diefes-Dux, H. A; Wan Salim, Wan Wardatul Amani (Elsevier BV, 2012)
A models and modeling perspective led to Model-Eliciting Activities (MEAs), authentic mathematical modeling problems, being introduced into a first-year engineering program in 2002. A design research perspective then led to iterative improvements in the design of these activities, strategies for their implementation, and strategies for assessing student work to promote effective learning across multiple learning objectives. This paper describes two different research threads that have lead to significant transformation of the first-year engineering experience. The first thread relates to problem formulation. The second thread relates to the dimensions along which instructors evaluate students’ open-ended problem solutions.